2006
DOI: 10.1007/s11249-006-9134-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electrochemistry on Surface Roughness during Chemical-Mechanical Polishing of Copper

Abstract: In this research, we investigated the electrochemical behavior of copper (Cu) surfaces during chemical-mechanical polishing (CMP) with alumina containing slurries. The variation of pH and the percent of oxidizer were tested against impressed anodic and cathodic potentials. The polarization curves as well as potential and current values were measured in order to investigate the effects of electrochemical interactions during polishing. The polishing performance was evaluated through friction, wear, and surface q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Results are discussed later. We have in the past reported effects of friction on oxidation of Cu during polishing [18][19][20][21] Figure 2. ͑Color online͒ ͑a͒ Friction coefficient of the tantalum sample in different electrolytes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results are discussed later. We have in the past reported effects of friction on oxidation of Cu during polishing [18][19][20][21] Figure 2. ͑Color online͒ ͑a͒ Friction coefficient of the tantalum sample in different electrolytes.…”
Section: Resultsmentioning
confidence: 99%
“…Details about this technique have been reported elsewhere. 19 The oxide thickness of the sample prepared through pure mechanical polishing was about 250 nm, while that of electrochemical-mechanical polishing was around 215 nm. It has been reported that the thickness of the native oxide of Ta is 2-3 nm.…”
Section: C14mentioning
confidence: 96%
“…The high friction distribution in region 1 is correlated with the Ra ͑surface roughness͒ value in a later section. Region 2 (pH [6][7][8][9][10][11][12][13][14].-Region 2 displays the alkaline pH and impressed anodic potential. Based on static etching experiments, we found that the dissolution of copper eventually stops at pH 6 or above.…”
Section: Resultsmentioning
confidence: 99%
“…The balance of thickness between oxidation and pad sweeping is, surface (108). If compounds were to form in the metal surface, electrochemical measurements, such as voltammetry can be used to detect them in situ.…”
Section: Kinetics Of Film Formationmentioning
confidence: 99%